Application of blender speed control technology in the processing of salak pondoh into coffee in Sibolong Hamlet - Iswanto Suwarno; Muhammad Ahmad Baballe; Irfan Ahmad; Erwin L. Rimban; Mohammad Aljanabi; Nia Maharani Raharja (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Dukuh Sibolong consists of nine RTs with a total population of 672. Based on the information our team got from Mr. Suharno as the head of the hamlet. The hamlet has several groups of informal community organizations such as youth organizations, PKK women. The majority of the population of Sonyo Hamlet are Muslim and have a livelihood as laborers, but there are also those who work as entrepreneurs because the geographical location of Sibolong Hamlet is located in the highlands. Actually, the hamlet of Sibolong has natural potential in the form of Salak Pondoh. One of these has just been processed into salak syrup. The potential of salak is managed by Mr. Suharno. Mr. Suharno has a market opportunity of up to 600 products per month. However, this opportunity brings consequences and problems, namely the wrong seed grinding machine is not owned. Information about some of the problems faced by the zalacca processors must of course be addressed as soon as possible as a solution for developing the zalacca processing business. The team that proposes service as part of the community who happens to be involved in the world of education, feels compelled to help provide solutions to the problems faced by Mr. Suharno's salak processing business. Through this proposed program of science and technology activities and based on the needs analysis that has been carried out, the service team tries to offer solutions to these problems with a touch of science and technology, namely through the main activity of designing a salak seed grinder to make salak coffee. The solosi is used to improve the processing of salak coffee.